PV2P: Program Visualization and Pair Programming to improve students understanding of Python programming / Syahrul Affendi Abdul Rahman - Abdul Rahman, Syahrul Affendi (Universiti Teknologi MARA, Kedah, 2023)
The objective of this research was to enhance the understanding of Python programming among students. The research involved 71 students from two form 2 classes at MRSM Tun Ghazali Shafie who were studying Basics of Computer Science (ASK) subject. The data collection is conducted through observation, pre- and post-tests, and questionnaires. Previously, students encountered difficulties in creating accurate computer program flowcharts and generating program code from the given flowchart. The students also could not solve the complex computer programming problems on their own. The pretest analysis revealed a mean score of 67.9 percent. Researchers evaluated the students' learning and introduced Program Visualization and Pair Programming (PV2P) method to enhance their understanding of Python programming. As a result, the post-test scores showed an increase to 85.3 percent, and the students responded positively to the questionnaires. Thus, PV2P was successful in improving the students' understanding of Python programming.